Fractional Calculus Operators and the Mittag-Leffler Function - Andrić, Maja (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on applications of the theory of fractional calculus in numerical analysis and various fields of physics and engineering. Inequalities involving fractional calculus operators containing the Mittag-Leffler function in their kernels are of particular interest. Special attention is given to dynamical models, magnetization, hypergeometric series, initial and boundary value problems, and fractional differential equations, among others.